Transition-Metal-Mediated Radiohalogenation using Aryl Boron Reagents - Burianova, Valeria K.; McErlain, Holly; Sutherland, Andrew (Synthesis, 2024)
Biomolecules labeled with radioisotopes of iodine and fluorine play a major role in science and medicine, with a range of applications including molecular imaging of disease, as radiopharmaceuticals for therapy and as tools for drug discovery. Due to the relative stability of Csp2–halogen bonds, radioiodine and radiofluorine labels are commonly incorporated into tracers via arene substitution. The wide availability of aryl boron reagents has led to their use for the development of radioiodination and radiofluorination methods, particularly using transition-metal complexes for accelerated reactions. Here, we review the range of transition-metal-mediated methods that have been developed for radiohalogenation of aryl boron compounds. Applications of these transformations for the preparation of molecular imaging agents and the use of new technologies to advance automated synthesis or high-throughput discovery are also described.1 Introduction2 Radioiodination Using Aryl Boron Reagents2.1 Applications of Copper-Mediated Radioiodination Reactions3 Radiofluorination Using Aryl Boron Reagents3.1 Radiofluorination Using Palladium, Nickel and Silver Complexes3.2 Radiofluorination Using Copper Complexes3.3 Applications of Copper-Mediated Radiofluorination Reactions3.4 New Technology for Copper-Mediated Radiofluorination Reactions4 Conclusions
Keywords: aromatic halogenation; radioiodine; radiofluorine; transition-metal catalysis; medical imaging